The Roman Lower Danube Frontier Innovations in Theory and Practice - Hanscam, Emily; Karavas, John (2024)
Over the past few decades, there has been a significant amount of research on the Roman Lower Danube frontier by international teams focusing on individual forts or broader landscape survey work; collectively, this volume represents the best of this collaboration with the aim of elevating the Lower Danube within broader Roman frontier scholarship.The Lower Danube, running between Singidunum (modern Belgrade) and Halmyris in the Danube Delta, was one of the most densely fortified regions of the Roman Empire. The region has long been a border zone, today forming part of the border between Serbia and Romania, and the majority of the border between Romania and Bulgaria. Despite its importance for understanding both Roman frontier policy and the relationship between ancient and modern borderscapes, the region has not yet made its full contribution to international Roman scholarship. Bridging the theoretical divide that exists between different regional research traditions, chapters in this volume focus on sites like Ratiaria, in modern north-western Bulgaria, while other contributors examine the complex landscape from a wider perspective oriented around roads, temporary camps, or early Christian sites. The Roman Lower Danube Frontier emphasises the importance of engaging with Roman frontier landscapes, particularly in regions such as East-Central Europe, where they remain part of a contemporary borderscape.